Degradation induced by TID radiation and hot-carrier stress in 130-nm short channel PDSOI NMOSFETs. (July 2017) - Dai, Lihua; Liu, Xiaonian; Zhang, Mengying; Zhang, Leqing; Hu, Zhiyuan; Bi, Dawei; Zhang, Zhengxuan; Zou, Shichang
Abstract: Hot-carrier reliability for devices operating in radiation environment must be considered. In this paper, we investigate how total ionizing dose impacts the hot-carrier reliability of partially-depleted SOI I/O NMOSFETs, highlighting the effect of buried oxide. Firstly, radiation-induced damage on short channel SOI devices with 100 nm thick Si film was investigated. After low total dose irradiation, incomplete fully-depleted state has been formed due to the non-uniformly distributed positive charges in the buried oxide. Furthermore, as the dominated factor of hot-carrier injection, the body current reduces after irradiation. Subsequently, the irradiated SOI devices were subjected to hot-carrier stress for 9000-s long time. Compared with unirradiated devices, the irradiated samples display enhanced hot-carrier degradation. We attribute this phenomenon to that radiation lowers the barrier for hot-carrier injection. Therefore, in order to ensure the reliability of SOI devices operating in harsh radiation environments, SOI devices with higher quality or corresponding hardness design should be taken. Highlights: After hot-carrier stress the irradiated devices display an enhanced degradation as compared to the unirradiated samples. Radiation lowers the barrier for hot-carrier-injection during hot-carrier stress. After irradiation the incomplete fully-depleted state has been formed due to the trapped positive charges in BOX. The body current reduces after irradiation.